Defining and classifying ecosystem services for decision making - Brendan Fisher; Robert Costanza; R. Kerry Turner; Morling Paul (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2007)
The concept of ecosystems services has become an important model for linking the functioning of ecosystems to human welfare benefits. Understanding this link is critical in decision-making contexts. While there have been several attempts to come up with a classification scheme for ecosystem services, there has not been an agreed upon, meaningful and consistent definition for ecosystem services. In this paper we offer a definition of ecosystem services that is likely to be operational for ecosystem service research and several classification schemes. We argue that any attempt at classifying ecosystem services should be based on both the characteristics of interest and a decision-context. Because of this there is not one classification scheme that will be adequate for the many context in which ecosystem service research may be utilized. We discuss several examples of how classification schemes will be a function of both ecosystem and ecosystem service characteristics and the decision-making context.
Keywords: 330; ecosystem benefits; Ecosystem services; environmental decision making; human welfare; Millennium Assessment; Umwelt; Natürliche Ressourcen; Nutzen; Wohlfahrtseffekt; Bewertung; Umweltpolitik